2019
DOI: 10.1016/j.atmosres.2019.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of the occurrence of African dust outbreaks on atmospheric pollutant levels in the Madrid metropolitan area

Abstract: The occurrence of African dust outbreaks over specific areas of the Mediterranean basin has been associated with increases in the PM 10 concentration levels and also in the mortality rates. Different hypothesis have been proposed in the last years to explain the processes by which African dust storms generates negative health effect over urban areas in southern Europe but are still not clear. Some authors have suggested the existence of an interaction between air pollutants from local sources and the occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
3
13
0
3
Order By: Relevance
“…Days with Saharan dust intrusion not only produce increases in concentrations of PM 10, they also result in increases in the concentrations of other pollutants such as NO 2 , although in our analysis, there were only statistically signi cant increases in Gran Canaria and Madrid. These results coincide with what has been found in other studies that analyze the evolution of primary pollutants on days with and without Saharan dust intrusion in the cities of Barcelona (Pandol et al, 2014) and Madrid (Salvador et al, 2019) and in other Spanish cities (Moreira et al, 2020). According to these studies, the reason for this increase is the existence of particulate material on days with Saharan dust intrusion, which produces a decrease in solar radiation and a consequent decrease in the convective turbulence processes that cause a vertical development of the mixing cap during the day.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Days with Saharan dust intrusion not only produce increases in concentrations of PM 10, they also result in increases in the concentrations of other pollutants such as NO 2 , although in our analysis, there were only statistically signi cant increases in Gran Canaria and Madrid. These results coincide with what has been found in other studies that analyze the evolution of primary pollutants on days with and without Saharan dust intrusion in the cities of Barcelona (Pandol et al, 2014) and Madrid (Salvador et al, 2019) and in other Spanish cities (Moreira et al, 2020). According to these studies, the reason for this increase is the existence of particulate material on days with Saharan dust intrusion, which produces a decrease in solar radiation and a consequent decrease in the convective turbulence processes that cause a vertical development of the mixing cap during the day.…”
Section: Discussionsupporting
confidence: 92%
“…Another possible hypothesis could be related to the fact that a decrease in the mixing cap is produced when there is a Saharan dust intrusion (Pandol et al, 2017;Salvador et al, 2019). A decrease in the mixing cap not only affects the increase in primary pollutants, including those we have included in this study, PM 10 and NO 2 , but it also makes the dispersion of other pollutants and increase in aerosols more di cult (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Days with Saharan dust intrusion not only produce increases in concentrations of PM 10 , they also result in increases in the concentrations of other pollutants such as O 3 . These results coincide with what has been found in other studies that analyze the evolution of pollutants on days with and without Saharan dust intrusion in the cities of Barcelona (Pandolfi et al 2014 ) and Madrid (Salvador et al 2019 ) and in other Spanish cities (Moreira et al 2020 ). According to these studies, the reason for this increase is the existence of particulate matter on days with Saharan dust intrusion, which produces a decrease in the convective turbulence processes that cause a vertical development of the mixing layer during the day.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the adverse health effects or toxicity of the locally produced particulate matter was also found to increase during dust outbreaks [21]. Studies in southern Europe (Barcelona and Madrid, Spain) have found that the mixing layer height significantly decreased with increasing intensity of Saharan dust events [22,23] and that an increased risk of mortality was observed with the reduction in mixing layer height [22]. This thinning of the mixing layer leads to an accumulation of local anthropogenic pollutants and may favour new particle formation or new species formed from condensation of gaseous precursors on the surface of dust particles [22,24].…”
Section: Introductionmentioning
confidence: 99%